Ewa Niesiołowska (1941-2013) - Płaza, Dominik Kacper; Papiernik, Piotr (Acta Archaeologica Lodziensia, 2018)
In this paper we would like to remember long-term curator of Archaeological and Ethnographical Museum in Lodz Ewa Niesiolowska. Ms. Ewa (how hers co-workers call her) worked in Museum of Lodz for almost 50 years and stared as assistant and finished as a curator. She was mostly interested in Mesolithic and Neolithic studies and was very friendly and helpful for us. She spend all Her professional life in Lodz Museum and we are sure that Ms Ewa deserves more than this short text.